The crystal structure of 4-(4-chlorophenyl)cyclohexane-1-carboxylic acid, C13H15ClO2 - Du Chao-Jun; Wang Zong-Dong; Wang Xiao-Ke; Zeng Yan (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C13H15ClO2, monoclinic, P21/n (no. 14), a = 14.4696(7) Å, b = 9.5385(4) Å, c = 18.7042(11) Å, β = 112.619(2)°, V = 2383.0(2) Å3, Z = 8, Rgt(F) = 0.0414, wRref(F2) = 0.1090, T = 150(2) K.